RESPON DAN MOTIVASI BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN TIMBAL BALIK (RECIPROCAL TEACHING) PADA MATA PELAJARAN IPA DI SMP NEGERI 4 BAWOLATO - Ekariyanti Zai; Destalena Libertini Lase; Agnes Renostini Harefa (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to find out how the response and motivation of students in reciprocal teaching learning, this study uses a quantitative method using an experimental design. Data collection was also carried out by distributing response questionnaires and students' learning motivation. This research was conducted at SMP Negeri 4 Bawalato in class VIII. Where is class VIII - A which will be applied to Reciprocal Teaching learning and class VIII - B which will be applied to conventional learning. Based on the research that has been done, the class VIII-A and class VIII-B students' learning responses in the Experiment class increased the percentage score from 39.26 to 94.2. However, in the control class there was a decrease in the percentage score from 37.93 to 37.13. As well as in the learning motivation of students in the experimental class before treatment, namely 40.13 to 94.6. In the control class there was a slight increase from the percentage score of 38.6 to 48.53. With this research, reciprocal teaching learning can increase students' responses and motivation.